Relationship between Permissive Parenting Style and Juvenile Delinquency in Senior High Schools: Hubungan antara Pola Asuh Orang Permisif Tua terhadap Kenakalan Remaja di Sekolah Menengah Atas - Ramadhani, Dea Lilla; Laili, Nurfi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the relationship between permissive parenting and juvenile delinquency at SMA Negeri 1 Mojosari. The variables in this study are permissive parenting as the dependent and juvenile delinquency as the independent. This study uses the Stratifed Sampling population in this study was 1,220 students and the sample used was 275 students. The measuring instrument of this study used the permissive parenting style scale and the juvenile delinquency scale. The reliability of the delinquency scale of permissive parenting is 0.817 and the juvenile delinquency scale is 0.865. Data analysis was carried out using descriptive analysis with a quantitative approach with the assistance of JASP. The results in this study indicate a correlation coefficient of Pearson's r= 0.69 with a significance value of < 0.001. It can be concluded that there is a positive relationship between permissive parenting and juvenile delinquency in SMA Negeri 1 Mojosari. This means that the higher the permissive parenting pattern, the higher the juvenile delinquency and vice versa, the lower the permissive parenting pattern, the lower the juvenile delinquency.